A Sn3Ag–CoSn3 composite copper pillar bump for three-dimensional packaging - JinTao Wang; YiNi Chen; ZiWen Lv; XiaoYu Han; ZiHan Pan; Feng Tian; MingYuan Zhao; HongBo Xu; GaoLiang Peng; HongTao Chen; MingYu Li (Journal of Materials Research and Technology)
Copper pillar bumps are widely utilized in advanced packaging technologies, representing a crucial foundation for 3D packaging. However, the mechanical properties of Sn3Ag bumps on copper columns often fall short of meeting increasingly demanding service conditions. Additionally, the loss of effectiveness due to excessive growth of intermetallic compounds at the interface needs to be addressed. To enhance the Sn₃Ag bumps and inhibit the excessive growth of intermetallic compounds, CoSn₃ nanocrystals were prepared, and Sn₃Ag–CoSn₃ composite copper pillar bumps were fabricated through composite electroplating. Upon reflowing, the CoSn3 nanocrystals decomposed, resulting in a significant formation of (Cu,Co)6Sn5 nanoparticles within the Sn3Ag matrix. The (Cu,Co)6Sn5 nanoparticles not only strengthen the solder joints by pinning, but also significantly reduced the excessive growth of interfacial intermetallic compounds, ultimately improving the service performance and reliability of the solder joints.